Phylogenomic evidence for ancient recombination between plastid genomes of the Cupressus-Juniperus-Xanthocyparis complex (Cupressaceae) - Andan Zhu; Weishu Fan; Robert P. Adams; Jeffrey P. Mower (BMC Evolutionary Biology, 2018)
Abstract Background Phylogenetic relationships among Eastern Hemisphere cypresses, Western Hemisphere cypresses, junipers, and their closest relatives are controversial, and generic delimitations have been in flux for the past decade. To address relationships and attempt to produce a more robust classification, we sequenced 11 new plastid genomes (plastomes) from the five variously described genera in this complex (Callitropsis, Cupressus, Hesperocyparis, Juniperus, and Xanthocyparis) and compared them with additional plastomes from diverse members of Cupressaceae. Results Phylogenetic analysis of protein-coding genes recovered a topology in which Juniperus is sister to Cupressus, whereas a tree based on whole plastomes indicated that the Callitropsis-Hesperocyparis-Xanthocyparis (CaHX) clade is sister to Cupressus. A sliding window analysis of site-specific phylogenetic support identified a ~ 15 kb region, spanning the genes ycf1 and ycf2, which harbored an anomalous signal relative to the rest of the genome. After excluding these genes, trees based on the remainder of the genes and genome consistently recovered a topology grouping the CaHX clade and Cupressus with strong bootstrap support. In contrast, trees based on the ycf1 and ycf2 region strongly supported a sister relationship between Cupressus and Juniperus. Conclusions These results demonstrate that standard phylogenomic analyses can result in strongly supported but conflicting trees. We suggest that the conflicting plastomic signals result from an ancient introgression event involving ycf1 and ycf2 that occurred in an ancestor of this species complex. The introgression event was facilitated by plastomic recombination in an ancestral heteroplasmic individual carrying distinct plastid haplotypes, offering further evidence that recombination occurs between plastomes. Finally, we provide strong support for previous proposals to recognize five genera in this species complex: Callitropsis, Cupressus, Hesperocyparis, Juniperus, and Xanthocyparis.